Changing the mix of healthcare providers : impact on price, efficiency and quality - Ryan, Padhraig G. (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2015)
Service providers, the personnel and organisations that deliver care, are the foundation of any health care system. The personnel include not only doctors, but pharmacists, nurses, and an array of allied health professions, while the organisations include hospitals, pharmacies, and ambulatory surgery centres. The configuration of providers influences dimensions of performance such as access, clinical quality, and value.
Keywords: Health Policy and Management, Ph.D.; Ph.D. Trinity College Dublin